Case report: Ventriculoperitoneal shunt disconnection resulting in migration of the distal catheter entirely into the abdominal cavity due to seizure - Yang, Xiang; Yang, Chaohua; Zhang, Yuekang (Frontiers in Surgery, 2022)
Ventriculoperitoneal (VP) shunt disconnection, a VP shunt complication, can be caused by several factors. We report the case of a young man who suffered VP shunt disconnection, and whose entire distal catheter migrated into the abdominal cavity due to a seizure. To our knowledge, risk factors for seizures related to shunt disconnection have not been previously evaluated. We report this rare case to highlight the fact that seizures are not negligible in increasing the probability of disconnection and migration of the entire distal catheter into the abdominal cavity. And the standardized treatment of traumatic seizures is extremely important.